Эффективность колхицина и выживаемость детей с амилоидозом почек при периодической болезни - Б. Е. Киракосян; Е. Б. Киракосян; В. Г. Оганесян; А. Х. Симонян (ՀՀ ԳԱԱ հրատ.)
Պարբերական հիվանդության ժամանակ ամիլոիդային նեֆրոպաթիայով տառապող երեխաների մոտ կոլխիցինով բուժման արդյունավետությունը կախված է ամիլոիդային նեֆրոպաթիայի շրջանից: There were investigated 190 children with renal amyloidosis in differrent stages undergoing colchicine therapy for evaluation of its efficiency. It was demonstrated that the treatment efficiency depends on the stage of the disease and the terms of colchicine application.
Keywords: Periodic Disease; Nephrology; Pediatrics